Electrode for redox flow battery and method for manufacturing electrode for redox flow battery
Patent Information
- Application Number
- JP2023503759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-05
- Filing Date
- 2022-02-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-02-24
AI Technical Summary
【0008】 本発明によれば、長期間の使用後も電極性能を維持できるレドックスフロー電池用電極、及びその製造方法を提供することができる。
Smart Images

Figure 0007642054000003 
Figure 0007642054000004 
Figure 0007642054000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a redox flow battery and a method for producing an electrode for a redox flow battery. [Background technology]
[0002] A redox flow battery, in which an electrolyte is supplied to electrodes to cause a battery reaction, typically comprises a battery cell including a porous positive electrode to which a positive electrolyte is supplied, a porous negative electrode to which a negative electrolyte is supplied, a membrane interposed between the two electrodes, and a non-impregnated current collector in contact with the porous electrode. Porous carbon electrodes are used as the electrodes from the viewpoints of acid resistance, electrolyte permeability, and electrical conductivity. The performance of carbon electrodes in redox flow batteries can be improved by surface modification of the electrodes to improve their wettability and reactivity with the electrolyte. Examples of such surface treatments that have been reported include a surface treatment of the electrode in ammonia (see, for example, Patent Document 1) and a surface treatment in which a carbon electrode on felt is covered with a melamine-based resin compound and baked at 500°C to cause nitrogen functional groups and oxygen functional groups to coexist (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] China Patent Application Publication No. 102487142 [Patent Document 2] China Patent Application Publication No. 110194453 Summary of the Invention [Problem to be solved by the invention]
[0004] In the reaction system in a redox flow battery, by modifying the electrode surface by introducing oxygen functional groups, it is expected that the wettability of the electrolyte solution will be improved and the reaction resistance between the electrode and the electrolyte will be reduced, but such modification alone will make the electrode performance more likely to deteriorate over long-term use. Specifically, although the initial battery performance will be high, the electrode performance will tend to deteriorate as the number of cycles increases. In particular, the electrode performance of the negative electrode is easily deteriorated. On the other hand, Patent Documents 1 and 2 propose a technique for improving electrode performance by modifying with various functional groups including nitrogen-based functional groups, but the carbon material nitrided under the conditions described in Patent Document 1 has a low degree of carbonization and a low degree of carbon crystallinity, so it is prone to excessive nitridation. In particular, when focusing on the examples in Patent Document 1, the proportion of surface carbon is less than 75% at the untreated stage. In Patent Document 2, the electrode is subsequently covered with a polymer containing nitrogen molecules and carbonized at a low temperature, so it is difficult to increase the firing temperature to leave elements other than carbon, the crystallinity of the coated carbon is low, and it is also difficult to increase the electrical conductivity of the coated part. Carbon materials with low crystallinity have concerns about their long-term electrical durability, but on the other hand, if the degree of carbonization is increased to increase the crystallinity, surface modification becomes difficult and it becomes impossible to ensure the wettability that is important in redox flow batteries. However, if a large amount of oxygen functional groups are introduced onto the surface to ensure wettability, the electronic conductivity is affected, resulting in a deterioration of performance, and excessive oxidation can lead to a significant weight loss and weakening of physical strength.
[0005] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and has an object to provide an electrode for a redox flow battery that can maintain electrode performance even after long-term use, and a method for producing the same. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by adjusting the surface functional group concentration in a redox flow battery electrode within a predetermined range, and have thus completed the present invention.
[0007] That is, the present invention includes the following aspects. [1] An electrode for a redox flow battery comprising a carbon structure, a carbon concentration of 82.0% or more and 98.0% or less, a nitrogen concentration of 1.0% or more and 10.0% or less, and an oxygen concentration of 1.0% or more and 8.0% or less, in a surface functional group concentration measurement of the carbon structure; [2] The electrode for a redox flow battery according to [1], wherein the carbon structure is a carbon foam having a three-dimensional network structure having continuous pores. [3] The electrode for a redox flow battery according to [1] or [2], wherein the carbon structure has a crystallite size Lc of 1.60 or more. [4] The electrode for a redox flow battery has a flow path shape for an electrolyte, The electrode for a redox flow battery according to any one of [1] to [3], wherein the flow path shape is formed by a flow section constituting a flow path and an electrode section in which the carbon structure is present in a film thickness direction. [5] The electrode for a redox flow battery according to [4], wherein an aspect ratio of a width a to a thickness z of the electrode portion, z / a, is less than 1.0. [6] The electrode for a redox flow battery according to [4] or [5], wherein a ratio of an occupied area A of the electrode portion to an occupied area B of the flow portion, expressed as A / B, is 1.0 or more. [7] A membrane-electrode junction material for a redox flow battery, comprising the electrode for a redox flow battery according to any one of [1] to [6] above, and an ion exchange membrane. [8] A positive electrode selected from the redox flow battery electrodes according to any one of [4] to [6]; an ion exchange membrane disposed on the positive electrode; a negative electrode disposed on the ion exchange membrane on the opposite side to the positive electrode and selected from the electrodes for redox flow batteries; Equipped with the flow channel portion and the electrode portion in the positive electrode and the negative electrode are disposed at the same position via an ion exchange membrane. [9] A redox flow battery comprising the electrode for a redox flow battery according to any one of [1] to [6] as a negative electrode.
[10] A method for producing an electrode for a redox flow battery having a carbon structure, comprising: a surface oxidation step of contacting a carbon material having a carbon concentration of 92.0% or more as determined by surface functional group concentration measurement with a first gas containing nitrogen and oxygen to obtain a carbon structure precursor; a surface modification step of contacting the carbon structure precursor with a second gas containing ammonia to obtain a carbon structure after the surface oxidation step; Including, The method for producing an electrode for a redox flow battery, wherein, in measurement of a surface functional group concentration of the carbon structure, an oxygen concentration is 1.0% or more and 8.0% or less.
[11] The manufacturing method for a redox flow battery according to
[10] , further comprising a carbonization step of heating the carbon material precursor at 1500° C. or more and 2500° C. or less to obtain a carbon material. Effect of the Invention
[0008] According to the present invention, it is possible to provide an electrode for a redox flow battery that can maintain electrode performance even after long-term use, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic diagram showing a porous carbon electrode having a comb-shaped flow channel as viewed from above in a plan view. [Diagram 2] FIG. 2 is a view of a porous carbon electrode having a comb-shaped flow channel shape, as viewed obliquely from above. [Diagram 3] FIG. 11 is a model diagram of a flow path shape viewed from above in a plane when determining the occupied area ratio. [Figure 4]FIG. 1 shows an image of the carbon foam electrode made in Example 1A. [Diagram 5] FIG. 13 is a diagram showing flow path portions provided on both ends of the carbon foam electrode produced in Example 1B. [Figure 6] FIG. 1 is a schematic diagram showing the carbon foam electrode prepared in Example 5A as viewed from above in a plan view. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention (hereinafter, also referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced with various modifications within the scope of the gist of the present invention.
[0011] [Electrodes for redox flow batteries] The electrode for a redox flow battery of this embodiment is an electrode for a redox flow battery comprising a carbon structure, and in a surface functional group concentration measurement of the carbon structure, the carbon concentration is 82.0% or more and 98.0% or less, the nitrogen concentration is 1.0% or more and 10.0% or less, and the oxygen concentration is 1.0% or more and 8.0% or less. Since the electrode for a redox flow battery of this embodiment is configured in this manner, it is possible to maintain the electrode performance even after a long period of use, and therefore, by applying it to a redox flow battery, it is possible to ensure the battery performance over a long period of time.
[0012] (Surface functional group concentration of carbon structure) In this embodiment, the surface functional group concentrations of the carbon structure are such that the carbon concentration is 82.0% or more and 98.0% or less, the nitrogen concentration is 1.0% or more and 10.0% or less, and the oxygen concentration is 1.0% or more and 8.0% or less. The carbon concentration is 82.0% or more, preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more, from the viewpoint of increasing the crystallinity and improving the long-term stability when used in a redox flow battery electrode, and is 98.0% or less, preferably 96% or less, and more preferably 94% or less, from the viewpoint of improving the wettability to the electrolyte and reducing the cell resistance. The nitrogen concentration is 1.0% or more, preferably 1.2% or more, and more preferably 1.5% or more from the viewpoint of improving long-term stability when used in a redox flow battery electrode, and is 10.0% or less, preferably 7.0% or less, and more preferably 5.0% or less from the viewpoint of improving wettability with respect to an electrolyte and reducing cell resistance. The oxygen concentration is 1.0% or more, preferably 2.0% or more, and more preferably 3.0% or more, from the viewpoints of improving wettability to the electrolyte and reducing cell resistance, and is 8.0% or less, preferably 7.0% or less, and more preferably 6.0% or less, from the viewpoints of improving the balance between initial electrode performance and long-term stability when used in a redox flow battery electrode. Here, the nitrogen concentration contributes to long-term performance maintenance when contained at a certain level or higher, but is not involved in improving crystallinity and generates defects in the skeleton, so that the properties of contributing as an element are closer to the behavior of oxygen than carbon. Therefore, as the relationship between the above carbon, oxygen, and nitrogen concentrations, taking into consideration long-term durability and wettability with the electrolyte, it is particularly preferable that the carbon concentration is 90% or more and the sum of the oxygen concentration and the nitrogen concentration is 10% or less. In this embodiment, from the viewpoint of further improving the long-term stability when used in a redox flow battery electrode, the nitrogen concentration is preferably at least one-fourth of the oxygen concentration, more preferably at least one-half of the oxygen concentration, and more preferably at most one-half of the oxygen concentration. Also, it is preferable that the nitrogen concentration is equal to or lower than the oxygen concentration. The surface functional group concentration can be measured by the method described in the Examples below. The surface functional group concentration can be adjusted to the above range, for example, by producing the product using the production method described below.
[0013] (Shape of carbon structure) The carbon structure in this embodiment can be used as an electrode for a redox flow battery, and as long as the above-mentioned surface functional group concentration is within a predetermined range, the shape, material, etc., of the carbon structure are not particularly limited, and various known shapes or materials can be adopted. In this embodiment, for example, carbon felt made of carbon fibers and carbon foam having a three-dimensional mesh structure with continuous pores can be adopted as the carbon structure, and these can typically be used in a sheet form. In this embodiment, the sheet form means a planar shape in which the smallest dimension of the three dimensions of length, width, and thickness for specifying the size of the carbon structure is the thickness. Since the carbon structure in this embodiment functions as a reaction field for directly exchanging electrons with the electrolyte, it is preferable that the carbon structure be a carbon foam having a three-dimensional mesh structure with continuous pores in order to ensure a uniform reaction in the cell.
[0014] (Thickness of carbon structure) The thickness of the carbon structure in this embodiment is not particularly limited, and can be, for example, 100 μm or more and 4000 μm or less. In this embodiment, when the carbon structure is a carbon felt made of carbon fibers, the thickness is preferably 1000 μm or more and 3000 μm or less. In addition, in this embodiment, when the carbon structure is a carbon foam having a three-dimensional network structure with continuous pores, the thickness is preferably 200 μm or more and 700 μm or less.
[0015] (Porosity of carbon structure) The porosity of the carbon structure in this embodiment is not particularly limited, and can be, for example, 70% or more and 99% or less. In this embodiment, when the carbon structure is a carbon felt made of carbon fibers, the porosity is preferably 87% or more and 97% or less from the viewpoints of flexibility and self-supporting property. In this embodiment, when the carbon structure is a carbon foam having a three-dimensional network structure with continuous pores, the porosity is preferably 85% or more and 95% or less from the viewpoints of flexibility and liquid permeability. The porosity can be calculated from the bulk density and the true density. The bulk density is a density based on the volume including the voids contained in the carbon structure. In contrast, the true density is a density based on the volume occupied by the carbon structure. The porosity Vf,pore can be calculated from the bulk density ρbulk and the true density ρreal using the following formula (1). Vf,pore=((1 / ρbulk)-(1 / ρreal)) / (1 / ρbulk)×100 (%) ···(1) In addition, the bulk density ρbulk and the real density ρreal can be calculated as follows.
[0016] [Measurement of bulk density] First, the dimensions of the carbon structure are measured using a caliper or the like, and the bulk volume Vbulk of the carbon structure is calculated from the obtained dimensions. Next, the mass M of the carbon foam is measured using a precision balance. From the obtained mass M and bulk volume Vbulk, the bulk density ρbulk of the carbon foam can be calculated using the following formula (2). ρbulk=M / Vbulk (2)
[0017] [True density measurement] The true density ρreal of the carbon structure can be determined by the sink-float method using a mixed solvent consisting of n-heptane, carbon tetrachloride, and ethylene dibromide. Specifically, first, a carbon structure of an appropriate size is placed in a stoppered test tube. Next, the three solvents are mixed appropriately and added to the test tube, and the mixture is placed in a thermostatic bath at 30°C. If the sample floats, the density is adjusted by adding n-heptane, which has a low density. On the other hand, if the test piece sinks, the density is adjusted by adding ethylene dibromide, which has a high density. This operation is repeated until the test piece floats in the liquid. Finally, the density of the liquid is measured using a Gay-Lussac pycnometer.
[0018] (Crystalline size of carbon structure Lc) In this embodiment, the crystal size Lc of the carbon structure is not particularly limited, but is preferably 1.10 nm or more, more preferably 1.60 nm or more from the viewpoint of electrical conductivity, and even more preferably 1.8 nm or more. In addition, from the viewpoint of ensuring sufficient physical strength, the crystal size Lc is preferably 4.0 nm or less, and more preferably 3.0 nm or less. The crystal size Lc can be measured by the method described in the Examples below. The crystal size Lc can be adjusted to the above range, for example, by increasing the carbonization temperature in the production method described below.
[0019] (Flow path shape) As described later, when the redox flow battery electrode of this embodiment is applied to a redox flow battery, a non-impregnated current collector plate that comes into contact with the redox flow battery electrode can be used. The non-impregnated current collector plate may be processed to have a flow path shape on its surface in order to reduce the pressure loss of the electrolyte by improving the flowability of the electrolyte. In particular, when the electrode thickness is 1.0 mm or less when the redox flow battery is produced, it is preferable to prevent an excessive increase in the pressure loss of the electrolyte by securing a certain amount of space in the electrode thickness direction and to secure the circulation of the electrolyte (hereinafter also referred to as "permeability"). From this viewpoint, when the electrode is compressed to a thickness of 1.0 mm or less, the redox flow battery electrode of this embodiment may have a flow path shape. When the flow path shape is formed in the redox flow battery electrode of this embodiment, rather than in the current collector plate itself, a cell can be easily assembled and measurements can be performed without using a bipolar plate with a flow path, which is difficult to process. In the present embodiment, the flow path shape is preferably formed from a flow section constituting the flow path and an electrode section in which the carbon structure is present in the film thickness direction. The flow section is a section in which the carbon structure is not present in the film thickness direction of the redox flow battery electrode, whereas the electrode section can be said to be a section in which the carbon structure is present in the film thickness direction of the redox flow battery electrode.
[0020] The shape of the flow path is not particularly limited, and shapes referred to in the present technical field as interdigitated or serpentine shapes can be adopted. In this embodiment, as shown in FIG. 1, a comb shape is preferable. It can be said that the flow path itself is an opposed comb shape, and the electrode part itself is a rectangular waveform (serpentine shape). Hereinafter, the flow path shape will be described based on the example of FIG. 1. Any direction in FIG. 1 can be said to be a surface direction perpendicular to the film thickness direction of the electrode for redox flow battery, and the electrode part and the flow path part are alternately arranged in this direction, and as a result, the electrode part itself has a serpentine shape, and the flow path part has a opposed comb shape. Hereinafter, a preferable flow path shape in this embodiment will be described, assuming that the thickness of the electrode for redox flow battery is z (hereinafter, also referred to as "film thickness z"), the average value of the width of the electrode part sandwiched between the flow paths as shown in FIG. 1 is a (hereinafter, also referred to as "width a of the electrode part"), and the average value of the width of the flow path part sandwiched between the electrode parts is b (hereinafter, also referred to as "width b of the flow path").
[0021] The width a of the electrode part is preferably 15 mm or less, more preferably 12 mm or less, and even more preferably 8 mm or less, from the viewpoint of improving the permeability of the electrolyte. The width a of the electrode part is preferably 1 mm or more, more preferably 3 mm or more, and even more preferably 4 mm or more, from the viewpoint of increasing the physical strength and maintaining ease of handling. As described above, the width a of the electrode portion is preferably 1 mm or more and 15 mm or less, more preferably 3 mm or more and 12 mm or less, and further preferably 4 mm or more and 8 mm or less.
[0022] The width b of the flow passage portion is preferably 0.5 mm or more, more preferably 1 mm or more, and even more preferably 1.5 mm or more, from the viewpoint of improving the permeability of the electrolyte. The width b of the flow passage portion is preferably 10 mm or less, more preferably 7 mm or less, and even more preferably 5 mm or less, from the viewpoint of ensuring the function of the electrode portion as an electrode. As described above, the width b of the flow portion is preferably 0.5 mm or more and 10 mm or less, more preferably 1 mm or more and 7 mm or less, and even more preferably 1.5 mm or more and 5 mm or less.
[0023] The width b of the flow portion and the width a of the electrode portion can be calculated by the method described in the Examples.
[0024] The film thickness z of the electrode for a redox flow battery is preferably 300 μm or more and 5000 μm or less. In order to show the film thickness z, a diagram of a redox flow battery electrode having a comb-shaped flow channel shape viewed obliquely from above is shown in FIG. By having the film thickness z be 300 μm or more, the permeability of the electrolyte can be improved, and the battery reaction field is increased, which tends to improve the battery cell performance. When used as an electrode for a redox flow battery, from the viewpoint of suppressing the electrolyte flow pressure loss, the film thickness z is more preferably 450 μm or more, and even more preferably 600 μm or more. Furthermore, by having the film thickness z be 5000 μm or less, the resistance in the electrode is suppressed, and the deterioration of the battery cell performance due to the increase in resistance tends to be suppressed. From the viewpoint of reducing the cell resistance, the film thickness z is more preferably 2500 μm or less, and even more preferably 1500 μm or less. As described above, the film thickness z is more preferably 450 μm or more and 2500 μm or less, and further preferably 600 μm or more and 1500 μm or less.
[0025] The aspect ratio z / a of the width a of the electrode part to the film thickness z is preferably less than 1.0, more preferably less than 0.8, and even more preferably less than 0.7, from the viewpoint of maintaining the independence of the electrode shape. The lower limit of the aspect ratio z / a is usually 0.03 or more, may be 0.05 or more, or may be 0.10 or more. The aspect ratio z / a is preferably 0.03 or more and less than 1.0, more preferably 0.05 or more and less than 0.8, and further preferably 0.10 or more and less than 0.7. The aspect ratio z / a of the width a of the electrode part of the carbon electrode to the film thickness z is preferably less than 1.0 when carbon foam is used. Moreover, when carbon foam or carbon paper is used, the aspect ratio z / a is preferably 0.03 or more and less than 1.0. When carbon felt is used, the aspect ratio z / a of the width a of the electrode part of the carbon electrode to the film thickness z is preferably less than 0.8, more preferably less than 0.6, and even more preferably less than 0.4. When carbon nonwoven fabric is used, the aspect ratio z / a is preferably 0.03 or more and less than 0.8, more preferably 0.05 or more and less than 0.6, and even more preferably 0.10 or more and less than 0.4.
[0026] The ratio b / a of the width a of the electrode part to the width b of the flow part is preferably less than 1.1, more preferably less than 0.9, and even more preferably less than 0.7, from the viewpoint of increasing the battery reaction field. The lower limit of the ratio b / a is usually 0.1 or more, and may be 0.3 or more, or 0.5 or more. The ratio b / a is preferably 0.1 or more and less than 1.1, more preferably 0.3 or more and less than 0.9, and even more preferably 0.5 or more and less than 0.7.
[0027] A model diagram of a redox flow battery electrode having a flow path shape as viewed from above in a plane is shown in Fig. 3. It is preferable to divide the regions as shown in Fig. 3 and adjust each calculated area value appropriately.
[0028] In this embodiment, it is preferable to adjust the ratio of the occupied area of the electrode part to the occupied area of the circulating part. The occupied area of the circulating part (meaning the total value when there are multiple circulating parts) corresponds to the region B in FIG. 3, and the area of the region B is also referred to as the area B. The occupied area of the electrode part corresponds to the region A in FIG. 3, and the area of the region A is also referred to as the area A. In this embodiment, the ratio of the area A to the area B, A / B, is preferably 1.0 or more, more preferably 1.4 or more, and even more preferably 1.8 or more. By having A / B of 1.0 or more, there is a tendency that the battery reaction field can be increased. From the viewpoint of ensuring the permeability of the electrolyte, the upper limit of A / B is preferably 20.0 or less, more preferably 10.0 or less, and even more preferably 5.0 or less. The ratio A / B is preferably 1.0 or more and 20.0 or less, more preferably 1.4 or more and 10.0 or less, and even more preferably 1.8 or more and 5.0 or less.
[0029] Generally, the cell chamber in a redox flow battery is rectangular, so when determining area B and area A, a minimum rectangular area C is set along the outermost periphery of the redox flow battery electrode. That is, area B can be determined by subtracting area A from the area of area C (hereinafter also referred to as "area C") surrounded by a thick outer frame in Fig. 3. Alternatively, area B can be calculated, and then area A can be determined by subtracting area B from area C.
[0030] The width a of the electrode portion, the width b of the flow portion, and the areas A to C can be measured by the method described in the Examples described later. However, if precise processing is possible, such as when forming a flow path using a Thomson punching die or performing laser processing using drawing data, the values of the width a of the electrode portion, the width b of the flow portion, and the areas A to C may be determined from design values of the Thomson punching die, drawing data, etc.
[0031] [Method for producing electrode for redox flow battery] The manufacturing method of the electrode for a redox flow battery of this embodiment (hereinafter also referred to as "the manufacturing method of this embodiment") is a manufacturing method of an electrode for a redox flow battery having a carbon structure, and includes a surface oxidation step of contacting a carbon material having a carbon concentration of 92.0% or more with a first gas containing nitrogen and oxygen to obtain a carbon structure precursor, and a surface modification step of contacting the carbon structure precursor with a second gas containing ammonia after the surface oxidation step to obtain a carbon structure, and the oxygen concentration is 1.0% or more and 8.0% or less in the measurement of the surface functional group concentration of the carbon structure. Since the manufacturing method of this embodiment is configured as described above, it is possible to manufacture an electrode for a redox flow battery that can maintain electrode performance even after long-term use.
[0032] (carbonization process) The manufacturing method of the present embodiment preferably further includes a carbonization step of heating the carbon material precursor at 2000° C. or more and 2500° C. or less to obtain a carbon material. That is, it is preferable to carry out a surface oxidation step after carrying out the carbonization step. When the heating temperature of the carbon material precursor is 2000° C. or more, the electrical conductivity of the carbon material and therefore the carbon structure tends to be improved, and when the heating temperature is 2500° C. or less, the physical strength tends to be sufficiently ensured.
[0033] (Surface oxidation process) In the surface oxidation step, a carbon material having a carbon concentration of 92.0% or more as measured by surface functional group concentration measurement is contacted with a first gas containing nitrogen and oxygen to obtain a carbon structure precursor. By including this step, a sufficient amount of oxygen and nitrogen functional groups can be introduced in the surface modification step described below, with the introduced oxygen functional groups acting as reaction initiation points, thereby achieving wettability and long-term electrolytic performance maintenance. When the carbon concentration is 92.0% or more, the electrical conductivity tends to be increased, and the carbon concentration is preferably 95% or more, and more preferably 98% or more. The composition of nitrogen and oxygen in the first gas is preferably nitrogen:oxygen=3.8:1, which is the same as the composition of air, but is not limited to this. The temperature conditions in the surface oxidation step are not particularly limited, but are preferably 300 to 700° C. The heating time that can be adopted in the surface oxidation step is preferably 0.5 to 3 hours, and more preferably 0.5 to 2 hours. When the heating time is 0.5 to 2 hours, there is a tendency that the initial electrode performance in terms of voltage efficiency can be improved.
[0034] (Surface modification process) In the surface modification step, the carbon structure precursor is contacted with a second gas containing ammonia to obtain a carbon structure. In the manufacturing method of the present embodiment, since the surface modification step is performed after the surface oxidation step, both the nitrogen functional group and the oxygen functional group can be added to the surface of the carbon structure without impairing the crystallinity of the carbon, and as a result, the long-term stability is improved when used in a redox flow battery electrode. The second mixed gas preferably contains ammonia and oxygen, and in this case, the blend ratio of ammonia and oxygen in the second gas is preferably between 16:1 and 1:3 ammonia:oxygen, more preferably between 8:1 and 1:3. When the blend ratio is between 8:1 and 1:3 ammonia:oxygen, the electrode performance tends to be higher even after long-term use. Nitrogen or argon may be introduced as an inert gas. Depending on the volume and structure of the furnace used, if the total amount of gas is small, it is difficult to control the stability of the process, so the total amount of gas can be adjusted by using an inert gas. The temperature conditions in the surface modification step are not particularly limited, but are preferably 300 to 700° C. Furthermore, the heating time that can be adopted in the surface modification step is preferably 0.5 to 2 hours.
[0035] (Method of forming flow channel shape) In the present embodiment, the flow path shape can be formed by preparing a sheet-shaped electrode for a redox flow battery as described above, and then punching the electrode with a Thomson punching blade, processing with a laser, processing by dicing, or the like. Among these, punching is preferred from the viewpoints of processing accuracy and processing speed. The shape of the flow path is preferably a rectangular shape when viewed from the film thickness direction from the viewpoint of deformation when assembled into a cell, but may be a triangular shape or a semicircular shape.
[0036] [Membrane electrode junction materials for redox flow batteries] The redox flow battery electrode of this embodiment can be used as a material for a redox flow battery, and can be used in combination with other battery components. For example, the redox flow battery electrode of this embodiment can be a composite material arranged on both sides of an ion exchange membrane. That is, the redox flow battery membrane-electrode junction material of this embodiment includes the redox flow battery electrode of this embodiment and an ion exchange membrane. Since the redox flow battery membrane-electrode junction material of this embodiment is configured as described above, it can maintain electrode performance even after long-term use, and therefore, by applying it to a redox flow battery, it is possible to ensure long-term battery performance.
[0037] The membrane-electrode bonding material for redox flow batteries of this embodiment can be manufactured by bonding, for example, by a hot press (also called heat press) method. That is, the membrane-electrode bonding material for redox flow batteries of this embodiment may be an embodiment in which the electrode for redox flow batteries is bonded to the ion exchange membrane by a hot press method. As a specific example of the hot press method, first, the ion exchange membrane and the porous carbon electrode are laminated, and placed between the pressure plates of a hot press machine together with a spacer of a desired thickness. Next, the pressure plate is heated to a predetermined temperature and then pressed. After holding for a predetermined time, the pressure plate is released, and the membrane-electrode bonding material for redox flow batteries is taken out and cooled to room temperature.
[0038] The heating temperature in the hot pressing method is preferably the glass transition temperature of the ion exchange membrane + 50°C or less, from the viewpoint that controlling the embedding depth of the carbon foam suppresses deterioration of the ion exchange membrane. The thickness of the spacer is preferably 30% to 90% and more preferably 50% to 80% of the total thickness of the carbon foam and the ion exchange membrane used. The holding time during pressing is preferably 0.5 minutes to 30 minutes and more preferably 2 minutes to 10 minutes.
[0039] The ion exchange membrane in this embodiment is preferably a membrane having a structure that allows the target ions to pass therethrough, and examples thereof include perfluorocarbon polymers having ion exchange groups and hydrocarbon membranes having ion exchange groups. Examples of ion exchange groups include, but are not limited to, -COOH groups, -SO3H groups, -PO3H2 groups, or salts thereof. Examples of salts include, but are not limited to, alkali metal salts, alkaline earth metal salts, and amine salts. Examples of resins include, but are not limited to, perfluorocarbon polymers and hydrocarbon membranes, and perfluorocarbon polymers are preferred from the viewpoint of good long-term durability.
[0040] The ion exchange membrane preferably has an equivalent mass EW of the ion exchange group of 600 g / eq or more and 2000 g / eq or less, from the viewpoint that suppression of permeation of active material ions improves current efficiency, and from the viewpoint that improvement of proton conductivity reduces resistance. The equivalent mass EW of the ion exchange membrane used in this embodiment is 600 g / eq or more, preferably 700 g / eq or more, more preferably 800 g / eq or more, and even more preferably 900 g / eq or more, from the viewpoint that the suppression of the permeation of the active material ions improves the current efficiency. In addition, the equivalent mass EW of the ion exchange membrane is 2000 g / eq or less, preferably 1700 g / eq or less, more preferably 1500 g / eq or less, and even more preferably 1200 g / eq or less, from the viewpoint that the improvement of the proton conductivity reduces the resistance. The equivalent mass EW of the ion exchange membrane is more preferably 700 g / eq or more and 1700 g / eq or less, more preferably 800 g / eq or more and 1500 g / eq or less, and even more preferably 900 g / eq or more and 1200 g / eq or less.
[0041] The equivalent weight EW means the dry weight (g) of the ion exchange membrane per equivalent of ion exchange group. The equivalent weight EW of the ion exchange membrane can be measured by salt-substituting the ion exchange membrane and back-titrating the solution with an alkaline solution. The equivalent weight EW can be adjusted by the copolymerization ratio of the monomers that are the raw materials of the ion exchange membrane, the selection of the monomer species, etc.
[0042] The thickness of the ion exchange membrane used in this embodiment is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 12 μm or more, because the shielding property of the active material when used as a battery is good. In addition, the thickness of the ion exchange membrane is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less, because the battery performance is improved by reducing the resistance. The thickness of the ion exchange membrane is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 100 μm or less, even more preferably 10 μm or more and 80 μm or less, and even more preferably 12 μm or more and 60 μm or less.
[0043] The thickness uniformity of the ion exchange membrane used in this embodiment is preferably within ±20% of the average thickness, more preferably within ±15%, and even more preferably within ±10%, from the viewpoint of reducing thickness unevenness of the ion exchange membrane and improving overall contact between the electrodes and current collector plates of the membrane electrode composite in order to uniformize the performance over the entire surface of the membrane electrode composite.
[0044] The thickness uniformity of the ion exchange membrane can be evaluated by leaving the ion exchange membrane in a temperature-controlled room at 23°C and a relative humidity of 65% for 12 hours or more, and then measuring the thickness at any 20 points using a contact-type thickness meter (e.g., manufactured by Toyo Seiki Seisakusho Co., Ltd.).
[0045] When preparing a membrane-electrode junction material for a redox flow battery, from the viewpoint of suppressing the contact resistance of the electrode interface during the preparation of a battery cell, it is preferable that the electrode part on the positive electrode side and the electrode part on the negative electrode side overlap in a large area when the ion exchange membrane is sandwiched between the positive electrode and the negative electrode, and it is further preferable that the formed flow paths have the same shape and are joined in the same shape with the ion exchange membrane sandwiched between them. That is, the membrane-electrode junction material for a redox flow battery of this embodiment includes a positive electrode selected from the electrodes for a redox flow battery of this embodiment, an ion exchange membrane arranged on the positive electrode, and a negative electrode arranged on the ion exchange membrane on the opposite side to the positive electrode and selected from the electrodes for a redox flow battery of this embodiment, and it is preferable that the circulation part and the electrode part in the positive electrode and the negative electrode are each arranged at the same position via the ion exchange membrane. The same is also preferable in the case where the ion exchange membrane and the electrode are not joined together.
[0046] [Redox flow battery] The electrode for a redox flow battery of this embodiment can be used, for example, as a cathode of a redox flow battery. That is, the redox flow battery of this embodiment can include the electrode for a redox flow battery of this embodiment as a negative electrode. Since the redox flow battery of this embodiment is configured as described above, it can maintain electrode performance even after long-term use, and therefore, by applying it to a redox flow battery, it is possible to ensure battery performance over a long period of time. The redox flow battery electrode of this embodiment can also be used as the positive electrode of a redox flow battery. When the redox flow battery electrode of this embodiment is used as the negative electrode, an electrode obtained by performing the surface oxidation step and not performing the surface modification step in the process of producing the redox flow battery electrode of this embodiment can also be used as the positive electrode.
[0047] The redox flow battery of this embodiment can typically have the following configuration: That is, an example of a redox flow battery includes an electrolytic cell including a positive electrode (positive electrode cell chamber), a negative electrode (negative electrode cell chamber), a diaphragm that separates the positive electrode cell chamber from the negative electrode cell chamber, and a non-impregnated current collector plate in contact with the electrodes, the positive electrode cell chamber contains a positive electrode electrolyte containing an active material, the negative electrode cell chamber contains a negative electrode electrolyte containing an active material, and the porous carbon electrode of this embodiment is used. EXAMPLES
[0048] The present embodiment will be described in more detail with reference to the following examples and comparative examples, but the present embodiment is not limited to the following examples in any way.
[0049] Example 1 As a carbon material precursor, melamine resin foam (dimensions: 400 mm x 400 mm x 40 mm, manufactured by BASF, product name "BASOTECT W") was placed around the sample using 1.2 mm thick SUS plates as spacers, sandwiched between 10 mm thick graphite plates from above and below, and introduced into a vacuum heat press machine (KVHC-II) manufactured by Kitagawa Seiki Co., Ltd. Next, the temperature inside the press machine was raised to 360°C at a heating rate of 5°C / min while evacuating with a vacuum pump, and held for 10 minutes. During the temperature rise and while holding at 360°C, pressing was performed at a pressure of 2.0 MPa. After that, the temperature inside the machine was lowered to 40°C, the vacuum pump was stopped, and the pressing was released. Next, a graphite plate with a thickness of 400 mm×400 mm×16 mm was placed on the pressed melamine resin foam, and a compressive load of 280 Pa was applied. The melamine resin foam was introduced into a heat treatment furnace (horizontal sintering furnace manufactured by IHI Corporation) while applying this compressive load. Next, nitrogen gas was supplied into the furnace at a flow rate of 2.5 L / min, and the temperature in the supply furnace was raised to a heat treatment temperature of 800° C. at a heating rate of 5° C. / min while simultaneously performing decompression and evacuation. Thereafter, the supply of nitrogen gas was stopped, and the temperature was raised to a heat treatment temperature of 2000° C. at a heating rate of 5° C. / min with the furnace vacuum degree being less than 10 Pa, and the pressed melamine resin foam was carbonized (carbonization process). Thereafter, the temperature in the furnace was lowered to room temperature, and the carbonized melamine resin foam (carbon material) was taken out from the furnace. The resulting melamine resin foam was then heat-treated at 600° C. for 1.5 hours in a dry air stream (surface oxidation step) to obtain a surface-oxidized melamine resin foam (carbon structure precursor). The carbon structure precursor was further heat-treated (surface modification step) at 640°C for 1 hour in a nitrogen:oxygen:ammonia mixed gas atmosphere (gas flow rates were 1.24 L / min:0.12 L / min:0.64 L / min, respectively) to produce a carbon structure further incorporating nitrogen functional groups. Such a carbon structure was used as electrode 1 and evaluated as described below. The carbon structure was examined using an X-ray CT (Rigaku, high-resolution 3D X-ray microscope nano3DX) and the bond density was found to be 2.0 × 10 6 pieces / mm 2The average orientation angle in the X direction was 66.4°, the average orientation angle in the Y direction was 50.6°, the average orientation angle in the Y direction was 54.4°, the minimum value of θd was 12°, and the ratio of nodes and lines Nl / Nn was 1.49. Furthermore, when the fiber diameter of the line portion was confirmed using an SEM (Hitachi Corporation, scanning electron microscope SU8010), it was found to be 1.8 μm on average. Furthermore, the thickness was measured using a vernier caliper, and the bulk density was calculated to be 164 kgm -3 The film thickness of the carbon structure of Example 1 was measured at 20 points using a contact type film thickness meter, and the average thickness was calculated to be 0.6 mm. Furthermore, the surface functional group concentration of the carbon material and the carbon structure was measured using an X-ray photoelectron spectrometer (VersaProbe II, manufactured by ULVAC-PHI, Inc.). At this time, the relative element concentration atomic% (hereinafter at%) of the main element peaks C1s peak near 285 eV, N1s peak near 400 eV, O1s peak near 533 eV, and Si2p peak near 104 eV was calculated and calculated as a percentage. If there was a peak with a large detection intensity among other element peaks, it was also calculated as a percentage (the same applies to the following Examples and Comparative Examples). That is, each surface functional group concentration was calculated as a percentage when the concentration of all detected functional groups was set to 100%. Details of the surface functional group concentration of the obtained carbon structure are shown in Table 1. In addition, the carbon concentration of the carbon material was measured in the same manner as above, and was 99.7%.
[0050] Example 2 The carbon structure precursor produced in Example 1 was used and heat-treated for 1 hour at 850° C. in an atmosphere of only ammonia gas (gas flow rate: 2 L / min) as a surface modification step. The obtained carbon structure was used as an electrode 2 and evaluated as described below.
[0051] Example 3 Carbon fiber felt (GFD4.6EA manufactured by SGL) was used as the carbon material, and was heat-treated at 600°C for 1 hour under a dry air stream (surface oxidation step) to obtain a carbon fiber felt (carbon structure precursor) with an oxidized surface. The carbon structure precursor was further heat-treated at 640°C for 1 hour under a nitrogen:oxygen:ammonia mixed gas (gas flow rates were 1.24L / min:0.12L / min:0.64L / min, respectively) atmosphere (surface modification step) to further introduce nitrogen functional groups and produce a carbon structure. The obtained carbon structure was used as electrode 3 and was evaluated as described below. The carbon concentration of the carbon material was 97.9%.
[0052] Example 4 A carbon structure was produced in the same manner as in Example 1, except that the treatment temperatures in the carbonization step, the surface oxidation step, and the surface modification step in Example 1 were changed as follows. Carbonization process: 1500℃, Surface oxidation process: 570℃, Surface modification process: 600℃. The carbon concentration of the obtained carbon material was 99.2%. The obtained carbon structure was used as an electrode 4 and was evaluated as described below.
[0053] Example 5 A carbon structure was produced in the same manner as in Example 3, except that carbon fiber felt (GFD1.5EA manufactured by SGL) was used as the carbon material for the electrode. The obtained carbon structure was used as electrode 5 and evaluated as described below. The carbon concentration of the carbon material was 98.0%.
[0054] Example 6 In the same manner as in Example 1, a carbonized melamine resin foam (carbon material) was prepared. The obtained melamine resin foam was then heat-treated (surface oxidation step) for 2.5 hours under a dry air stream at 600°C to obtain a melamine resin foam (carbon structure precursor) with a larger surface oxidation amount than in Example 1. Thereafter, the surface modification step was carried out under the same conditions as in Example 1. The obtained carbon structure was used as an electrode 6 and evaluated as described below.
[0055] Example 7 In the same manner as in Example 1, a carbonized melamine resin foam (carbon material) was prepared. Subsequently, the obtained melamine resin foam was heat-treated at 600° C. for 2.0 hours in a dry air stream (surface oxidation step), thereby obtaining a melamine resin foam (carbon structure precursor) having a surface oxidized in accordance with Example 1. Next, the carbon structure precursor was heat-treated (surface modification step) at 650°C for 1.5 hours in an atmosphere of nitrogen:oxygen:ammonia mixed gas (gas flow rates were 1.00 L / min:0.06 L / min:0.94 L / min, respectively) to produce a carbon structure with nitrogen functional groups introduced therein. The obtained carbon structure was used as electrode 7 and was evaluated as described below.
[0056] Comparative Example 1 A redox flow battery evaluation described below was performed without carrying out a surface modification step, using the carbon structure precursor produced in Example 1. The carbon structure precursor was used as an electrode 8 and the evaluation described below was performed.
[0057] Comparative Example 2 The carbon structure precursor prepared in Example 1 was heat-treated at 650° C. for 3 hours under a dry air stream without being subjected to a surface modification step, thereby obtaining a carbon structure precursor with an excessively oxidized surface. The carbon structure precursor was used to perform the redox flow battery evaluation described below. The carbon structure precursor after excessive oxidation was used as an electrode 9 and the evaluation described below was performed.
[0058] Comparative Example 3 A redox flow battery evaluation described below was carried out without carrying out a surface modification step by using the carbon structure precursor produced in Example 3. The carbon structure precursor was used as an electrode 10 and the evaluation described below was carried out.
[0059] <Evaluation of crystallite size> The crystallite size Lc was evaluated from the diffraction of the (002) plane of electrodes 1 to 10 produced in Examples 1 to 7 and Comparative Examples 1 to 3. After the samples were crushed in a mortar, wide-angle X-ray diffraction of the crushed samples was measured using a tabletop X-ray diffractometer D2 PHASER (manufactured by Bluker). The specific measurement conditions were as follows: [Measurement conditions] Source: Cu Kα Bulb current: 30mA Tube voltage: 40kV Slit: 1mm Sample rotation speed: 10 rpm Measurement time for one step: 0.3 sec Starting angle (2θ): 5.00° Measurement step (2θ): 0.01° End angle (2θ): 90.00°
[0060] After the above measurements, the obtained data was analyzed to calculate the crystallite size Lc. The crystallite size Lc was calculated by substituting the half-width β of the (002) diffraction peak appearing near 2θ = 25 degrees and the angle θ of the peak maximum value into the Scherrer formula (formula (A) below). Generally, the higher the temperature at which carbonization is performed, the higher the crystallinity and the larger the Lc value. Lc = (Kλ) / βcosθ (A) In the above formula (A), K is the shape factor and λ is the wavelength of the radiation source. Since the shape factor is the (002) plane diffraction, 0.90 was substituted, and since CuKα was used as the radiation source, 1.541 was substituted and the calculation was performed. The results are shown in Table 1.
[0061] <Redox flow battery evaluation> Redox flow batteries were fabricated using the electrodes 1 to 10 fabricated in Examples 1 to 7 and Comparative Examples 1 to 3, and performance evaluation was carried out. That is, the following evaluation cells were prepared. A cell was used that was composed of an EPDM rubber gasket, a polyvinyl chloride frame, a graphite separator (width: 2 mm, material: G-347) with a comb-shaped flow path, and a copper end plate. However, the cells of electrodes 3 and 5 used flat graphite separators (material: G-347) without flow paths. Nafion212 purchased from Aldrich was used for the ion exchange membrane. The gasket was adjusted in thickness so that the electrode compression ratio was 60%. The ion exchange membrane cut to 40 mm x 90 mm, two carbon structures (electrodes 1 to 10) punched to 25 mm x 20 mm, and cell components were combined in a specified order and fastened with a specified torque using stainless steel bolts. The assembled cell was connected to an electrolyte circulation device composed of an electrolyte tank and a liquid delivery pump. 30 mL of a vanadium sulfate solution with a vanadium ion concentration of 1.5 mol / L, vanadium ion valence of 3.5, and sulfate ion concentration of 4.5 mol / L was added to the electrolyte tank and circulated at a flow rate of 7.5 mL / min. The charge / discharge test was performed using a bipolar power supply manufactured by Kikusui Electronics Co., Ltd. under a constant current method. The voltage range was 1.00 to 1.55 V, and the current density was 80 mA / cm. 2 The current efficiency CE, voltage efficiency VE, and power efficiency EE were calculated from the charge capacity Qc, discharge capacity Qd, average charge voltage Vc, and average discharge voltage Vd at the 50th and 200th cycles, respectively, using the following formulas. These results are also shown in Table 1. CE: Qd / Qc(%) VE: Vd / Vc(%) EE:CE×VE(%)
[0062] The evaluation results of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 1 below.
[0063] [Table 1]
[0064] Example 1A The following flow channel processing was carried out on the electrode 1 produced in Example 1 in order to give a comb-shaped flow channel shape as shown in Fig. 4. When the shape in Fig. 4 is viewed from above, each region can be divided as shown in Fig. 3, and the value corresponding to area C in Fig. 3 was 34 mm x 30 mm. The width b of the flow-through portion was 2.0 mm, and punching was performed using a Thomson punching blade (manufactured by Nagoya Blade Co., Ltd.) configured to provide seven flow-through portions each having a length of 30 mm in the direction perpendicular to the width b of the flow-through portion (electrolyte flow direction), to obtain an electrode 1A having a flow channel shape as shown in Figure 4. The thickness (film thickness z), width (width a of the electrode portion and width b of the flow-through portion), and area of each region (areas A to C) of the obtained electrode 1A were confirmed based on the measurement method shown below. Furthermore, the obtained electrode 1A was subjected to a redox flow battery evaluation described later.
[0065] (film thickness z) The thicknesses at the four corners of the electrode 1A were measured using a contact type film thickness meter (for example, manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the average film thickness z was measured by adding up the measured values and dividing them again.
[0066] (Width of electrode part a) The width of the electrode was measured using a microscope (Keyence VHX-950F), and the width a of the electrode was calculated by adding up the measured widths and dividing them. The measurement position was set to be near the center, which is almost equidistant from both ends.
[0067] (Width of circulation section b) The width of the entire flow groove was measured using a microscope (Keyence VHX-950F), and the total width was added up and divided to calculate the width b of the flow section. The measurement position was set at the center, which was approximately the same distance from both ends.
[0068] (Area A~C) Using a ruler, the area C corresponding to region C in Figure 3 was measured. Furthermore, the width of the unmeasured portion was measured using a ruler or a microscope (Keyence VHX-950F), and areas A and B in Figure 3 were measured and calculated. All values were in good agreement with the values (design values) of the Thomson punching die.
[0069] <Redox flow battery evaluation> The performance of the redox flow battery was evaluated in the same manner as described above, except that the evaluation conditions were changed as follows: The graphite separator (width: 2 mm, material: G-347) with a comb-shaped flow path was changed to a flat graphite separator (material: G-347) without a flow path, and the gasket was adjusted to have the film thickness when assembled into the cell shown in Table 2. In addition, an ion exchange membrane cut to 50 mm x 100 mm and a carbon structure (electrode 1A) with a flow path formed by punching to a size of 34 mm x 30 mm were used.
[0070] <Liquid permeability> In the above redox flow battery evaluation, the one in which the electrolyte was circulated was evaluated as having liquid permeability. The one in which the electrolyte was not circulated was evaluated as not having liquid permeability. The evaluation results are shown in Table 2. In the table, ◯ indicates that liquid permeability was ensured, and × indicates that liquid permeability was not ensured.
[0071] Example 1B Flow paths were processed in the same manner as in Example 1A, except that the Thomson punching blade was changed as follows. That is, the width b of the flow path was 1.0 mm, and seven flow paths each having a length of 32 mm in the direction perpendicular to the width b of the flow path (electrolyte flow direction) were punched out using a Thomson punching blade configured to provide the flow paths, to obtain an electrode 1B having a comb-shaped flow path shape. In Example 1B, flow path grooves were provided on both ends of the electrode as shown in FIG. 5. The obtained electrode 1B was measured in the same manner as in Example 1A, and the results are shown in Table 2.
[0072] Example 1C Two sheets of the electrode 1A produced in Example 1A were stacked and then pressed together to obtain an electrode 1C. The electrode 1C was measured in the same manner as in Example 1A, and the results are shown in Table 2.
[0073] Example 5A Flow paths were processed in the same manner as in Example 1A, except that the electrode 5 prepared in Example 5 was used instead of the electrode 1, and the Thomson punching blade was changed as follows. That is, the width b of the flow path was 3.0 mm, and punching was performed using a Thomson punching blade configured to provide four flow paths each having a length of 30 mm in the direction perpendicular to the width b of the flow path (the direction of flow of the electrolyte), to obtain an electrode 5A having a comb-shaped flow path shape (see FIG. 6). The electrode 5A was measured in the same manner as in Example 1A, and the results are shown in Table 2.
[0074] Comparative Example 1A Electrode 8A was obtained in the same manner as in Example 5A, except that electrode 8 produced in Comparative Example 1 was used instead of electrode 5. Electrode 8A was measured in the same manner as in Example 1A, and the results are shown in Table 2.
[0075] [Table 2]
[0076] This application is based on a Japanese patent application (Patent Application No. 2021-035448) filed on March 5, 2021, the contents of which are incorporated herein by reference.
Claims
1. A method for producing an electrode for a redox flow battery having a carbon structure, comprising: a surface oxidation step of contacting a carbon material having a carbon concentration of 92.0% or more as determined by surface functional group concentration measurement with a first gas containing nitrogen and oxygen to obtain a carbon structure precursor; a surface modification step of contacting the carbon structure precursor with a second gas containing ammonia to obtain a carbon structure after the surface oxidation step; Including, wherein, in a surface functional group concentration measurement of the carbon structure, the oxygen concentration is 1.0% or more and 8.0% or less.
2. The method for producing a redox flow battery according to claim 1, further comprising a carbonization step of heating the carbon material precursor at 1500° C. or more and 2500° C. or less to obtain a carbon material.
Citation Information
Patent Citations
Electrode for flow energy storage battery
CN102487142A
Modified carbon material and nitrogen-rich liquid flow battery electrode prepared from modified carbon material
CN110194453A
Carbon electrode material assembly
JP2001085021A
Electrode material for redox flow battery
JP2017027918A
Redox flow cell
JP2020077540A